Impact of 2007- 2009 Global Financial Crisis on Cocoa Exportation in Nigeria - Ojong, C. M.; Bassey, Bernard Esor-Eze; Anthony, Ogar (Advances in Social Sciences Research Journal, 2016)
The essence of this study is to examine the impact of the global financial crisis of 2007- 2009 on cocoa production in Nigeria. Although the crisis had its roots in American financial markets, it percolates very rapidly to other economies throughout the entire global financial markets through several transmissions medium. Our main concern was to determine if the crisis in question created any structural changes in cocoa export in Nigeria or not. To achieve our objectives, we collected data spanning from 2004 to 2014. Subsequently we divided our sample into two subsamples- pre crisis period, post crisis period and applied the least square technique to the two subsamples and the pooled sample to test the statistical significance of all the identified variables. It appears that the crisis did not produce any structural changes in cocoa export in Nigeria. In the light of this finding, it is our considered opinion that Cocoa export offers alternate source of stable foreign exchange earnings that is immune from negative demand shocks and vagaries of uncertainty. Therefore, it behooves on the Nigerian policy makers to evolve policies that will promote Cocoa production in order to diversify the Nigeria economy and forestall the drift that Crude oil price volatility has exposed her economy to.